Do Moskvy daleko . Do Moskvy daleko . Far From Moscow . До Москвы далеко - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Second anniversary of the proclamation of the Altai Republic; Altai's economic problems. Featured in the program: Mazaev, Vladimir (People's Deputy); Tikhonov, Vladimir (People's Deputy) Contributors: Tolstykh, Evgenii (Anchor) Вторая годовщина провозглашения республики Алтай; экономические проблемы Алтая. В программе участвуют: Мазаев, Владимир (Народный депутат); Тихонов, Владимир (Народный депутат) Создатели: Толстых, Евгений (Ведущий/Ведущая)